The Possibility of Using Navigation GPS Devices in the Survey Engineering - Abbas Neam Al dami, Haidar; Riyadh Abdulridha, Isaraa (International Journal of Engineering and Technology, 2018)
As a result of the tremendous development in the field of computer technologies, communications and information revolution, new applications which has seen a tremendous development in terms of devices and technologies used in various applications such as a device Electronic Distance Measurement (EDM), Total Station, GPS (Surveyor and Navigational)… etc. In this study, five-ground control points (BM) were made to provide traverse, and these points observed by using three different navigation GPS devices, and observed by using TOTALSTATION device, and using spatial and statistical analysis functions in GIS.  The study showed that the error in these devices is a random error varies from one device to another. In addition, it showed that the error varies from time to time. Cannot be determined the spread of readings to the observed point (by navigation GPS) in a particular direction or specific frame, as well as the central distance of the readings are changing from one device to another and from point to point.The study recommends that should not be used navigation GPS devices in the survey work.  In addition, re-survey all areas are observed or defined its borders by using this device (navigation GPS) by serving GPS devices with the required accuracy.